1990
DOI: 10.1007/bf01537222
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of loxiglumide (CCK antagonist) inhibits postprandial gallbladder contraction without affecting gastric emptying

Abstract: The effect of a single oral dose of loxiglumide, a cholecystokinin antagonist, on postprandial gallbladder contraction and on gastric emptying was evaluated in humans. Following a 12-hr fasting period, two tablets of loxiglumide (400 mg each) or placebo was administered on different days, in random order and in a double-blind fashion to 10 healthy volunteers 15 min before the ingestion of a 1050-kcal standard meal. Gallbladder and antral volumes were measured by real-time ultrasonography in basal conditions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 20 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…However, the effect of CCK antagonists on gastric emptying remains controversial. Although several studies have shown gastric emptying to be accelerated by CCK antagonists (14 -16), two other studies failed to demonstrate an increase in gastric emptying rates (17,18). Nevertheless, current data would suggest a close interaction between nutritional status, CCK, and gastric emptying.…”
mentioning
confidence: 49%
“…However, the effect of CCK antagonists on gastric emptying remains controversial. Although several studies have shown gastric emptying to be accelerated by CCK antagonists (14 -16), two other studies failed to demonstrate an increase in gastric emptying rates (17,18). Nevertheless, current data would suggest a close interaction between nutritional status, CCK, and gastric emptying.…”
mentioning
confidence: 49%
“…Feedback regulation of CCK release by intraluminal protease activity is probably of minor importance. It has to be noticed that loxiglumide does not elevate basal plasma IR-CCK levels, despite its pronounced effect on fasting gallbladder volume [ 18,19,26]. Only meal-stimulated CCK secretion is further augmented by the receptor antagonist.…”
Section: Discussionmentioning
confidence: 98%
“…However, this interpretation remains speculative, since gastric emptying was not measured in the present study. The role of CCK in gastric transit in man remains ill-defined, because controversial results have been reported employing different CCK receptor antagonists and different methods for the estimation of gastric emptying rate [16,17,19]. A direct stimulation of insulin release by CCK has been well documented in rats and dogs, but only at supra-physiological doses [5-71.…”
Section: Discussionmentioning
confidence: 99%
“…However, no immunohistochemical studies are yet available to provide anatomical evidence for this pathway. In contrast, a recent study even suggests the existence of a peripheral inhibitory pathway, as both phrenectomy and vagotomy did not prevent crural diaphragm inhibition during oesophageal distension 49–51 …”
Section: Crural Diaphragmmentioning
confidence: 90%